2021
DOI: 10.1108/oir-11-2020-0514
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors of participants' attitudes toward the ethics of social media data research

Abstract: PurposeThe purpose of this study was to investigate the participants' attitudes toward the ethical issues caused by collecting social media data (SMD) for research, as well as the effects of familiarity, trust and altruism on the participants' attitudes toward the ethics of SMD research. It is hoped that through this study, scholars will be reminded to respect participants and engage in ethical reflection when using SMD in research.Design/methodology/approachThis study adopted social media users as its researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(68 reference statements)
1
4
0
Order By: Relevance
“… 27 suggest, educating the public about why research is important and why it requires their data is vital to ensuring individuals’ comfort with their data being used. As earlier studies 11 , 24 and now our work show, how much data sharers trust researchers affects their perceptions of acceptable use. People who place more trust in institutions were more likely to accept their data being used.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“… 27 suggest, educating the public about why research is important and why it requires their data is vital to ensuring individuals’ comfort with their data being used. As earlier studies 11 , 24 and now our work show, how much data sharers trust researchers affects their perceptions of acceptable use. People who place more trust in institutions were more likely to accept their data being used.…”
Section: Discussionsupporting
confidence: 60%
“…For example, a study about UK public health research found that when participants were told that mandating consent could lead to selection bias and adversely impact public health research, participants were more willing to share their data without explicit consent 21 . For both health data 21 23 and social media data 11 , 24 , how much participants believe that sharing their data will contribute to a purpose that will benefit society affects how acceptable they find the use of their data.…”
Section: Factors Affecting Perceptions Of Acceptable Usementioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as early as 1997, Nissenbaum (1997) proposed that the protection of privacy should not ignore the noninitiate realm. Other studies have confirmed with empirical data that social media users have strong ethical needs, and ethical attitudes will change with changes in researchers' behavior (Chen et al, 2021a). Therefore, the random collection of personal information on public platforms may infringe on users' privacy, lead to a chilling effect and inhibit free expression.…”
Section: Researchers Cannot Assume User Consentmentioning
confidence: 87%
“…The focus of Sebastião et al's [37] research was to assess public relations practitioners' attitudes towards their professional use of social networks. Chen et al [44] investigated the deter-mining factors of the participants' attitudes towards social network data research ethics. Brady et al [45] have developed a method to measure expressions of moral outrage at the level of texts used on social networks.…”
Section: Ethical Attitude Towards Social Networkmentioning
confidence: 99%